1976
DOI: 10.1093/ageing/5.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Cephazolin Treatment of Pneumonia in the Elderly

Abstract: Cephazolin, a semi-synthetic cephalosporin for parenteral use, was evaluated in 39 elderly hospital patients. Thirty-three of these patients were seriously ill at the start of treatment, suffering from pulmonary infections. In the other six patients, the drug was used post-operatively as a prophylactic, and it was effective in all cases in preventing any subsequent infection. Cephazolin was very effective in the treatment of 27 of the severely ill patients; the primary pathogen was eradicated and there was goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…We included 30 primary studies that assessed the frequency of cefazolin allergy in series of patients with self-reported or confirmed penicillin allergy (Table 1). The included primary studies had been published between 1976 and 2020, assessing a total of 6001 participants. In 9 studies, penicillin allergy was confirmed by diagnostic testing (skin, in vitro, and/or drug challenges).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 30 primary studies that assessed the frequency of cefazolin allergy in series of patients with self-reported or confirmed penicillin allergy (Table 1). The included primary studies had been published between 1976 and 2020, assessing a total of 6001 participants. In 9 studies, penicillin allergy was confirmed by diagnostic testing (skin, in vitro, and/or drug challenges).…”
Section: Resultsmentioning
confidence: 99%
“…In 9 studies, penicillin allergy was confirmed by diagnostic testing (skin, in vitro, and/or drug challenges). In 13 studies, cefazolin allergy was assessed by means of skin tests or drug challenges, whereas prophylactic or therapeutic introduction of cefazolin occurred in 18 studies …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation